ADAB PESERTA DIDIK KEPADA GURU DALAM SURAT AL-HUJURAT AYAT 1-5 - Munzillah, Indiarti Muafiqoh; Fauzi, Sriyono (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2023)
Education is very important for everyone because with education, there will also be more knowledge and knowledge that is known and owned and understood. Education is not only in formal institutions but from non-formal institutions. The world of education requires scientific education, technology that continues to advance and generations that alternately create different civilizations and characters. Technology that is increasingly advanced if used in a good direction will aim well, while if used in bad things then it will have a bad impact on himself or the target. Technology is one element in the world of education, namely the element of educational tools. Based on the explanation above, the author is interested in examining the adab of students to teachers in Surah Al-Hujurat verses 1-5, so the purpose of this study is to describe the adab of students to teachers contained in Surah Al-Hujurat verses 1-5. This research uses qualitative research methods with a literature model. The stages in analyzing data are doing it by reducing data, presenting data, and drawing conclusions.